Memprediksi Financial Distress melalui Faktor Internal pada Perusahaan Jasa Sub Sektor Property dan Real Estate - Suryani Suryani; Desy Mariani (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
This study aimed to analyze the effect of profitability, leverage, liquidity, activity, and cash flow ratio towards financial distress. The population in this study is property and real estate of the service company by using the purposive sampling technique. The research sample obtained was 180 samples from 45 companies. The analysis technique used is multiple linier regression analysis. The results showed that profitability, activity, and cash flow ratio had no effect towards financial distress. leverage had a negative effect and significant towards financial distress. and liquidity has a positive effect and significant towards financial distress.